Middle Eocene large coccolithaceans: Biostratigraphic implications and paleoclimatic clues - Cappelli, C; Agnini, C; Bown, PR; De Riu, M (Elsevier BV, 2020)
A combined light microscope-scanning electron microscope study of exceptionally well-preserved calcareous nannofossil assemblages from clay-rich middle Eocene sediments recovered at IODP Site U1410 (NW Atlantic Ocean) has enabled us to document a new evolutionary lineage within Coccolithus-like placoliths that have well-developed near-axial or diagonal cross-bars in their central-area. Based on our observations, we describe a new genus Pletolithus, a new species Pletolithus giganteus and four new combinations (Pletolithus opdykei, Pletolithus staurion, Pletolithus mutatus and Pletolithus gigas). The distinctive ultra-structures of the different morphotypes and the presence of transitional morphologies suggest that Pletolithus evolved from a morphological variant of Coccolithus. The evolution of this group of coccolithaceans is initially characterized by increasing size and the appearance of delicate axial cross-bars in the central-area. Size continues to increase in these coccoliths and the orientation of the cross-bars shifts to asymmetric and diagonal in later representatives. Morphometric measurements on P. gigas and the morphologically similar P. giganteus, provide evidence for the presence of two distinct populations allowing for an objective differentiation of these two species, which in turn provides unambiguous taxonomic definition for the important biostratigraphic marker species P. gigas. These data improve the reliability of middle Eocene biostratigraphy and show that this lineage appeared when a new equilibrium in the environmental conditions was reached and intriguingly it coincides with a remarkable change in the deep circulation of the North Atlantic Ocean.